Chemo‐ and Enantioselective Oxidative α‐Azidation of Carbonyl Compounds. Issue 39 (6th August 2020) - Uyanik, Muhammet; Sahara, Naoto; Tsukahara, Mayuko; Hattori, Yuhei; Ishihara, Kazuaki
Abstract: We report high‐performance I + /H2 O2 catalysis for the oxidative or decarboxylative oxidative α‐azidation of carbonyl compounds by using sodium azide under biphasic neutral phase‐transfer conditions. To induce higher reactivity especially for the α‐azidation of 1, 3‐dicarbonyl compounds, we designed a structurally compact isoindoline‐derived quaternary ammonium iodide catalyst bearing electron‐withdrawing groups. The nonproductive decomposition pathways of I + /H2 O2 catalysis could be suppressed by the use of a catalytic amount of a radical‐trapping agent. This oxidative coupling tolerates a variety of functional groups and could be readily applied to the late‐stage α‐azidation of structurally diverse complex molecules. Moreover, we achieved the enantioselective α‐azidation of 1, 3‐dicarbonyl compounds as the first successful example of enantioselective intermolecular oxidative coupling with a chiral hypoiodite catalyst. Abstract : High‐performance hypoiodite catalysis was developed for the chemoselective oxidative or decarboxylative oxidative α‐azidation of 1, 3‐dicarbonyl compounds (see scheme). By this method, the late‐stage azidation of complex molecules with NaN3 and hydrogen peroxide as the azide source and oxidant, respectively, was possible under extremely mild conditions.